CULTIVATION OF PLANTING AND FERTILIZATION TECHNIQUES ON ZEA MAYS CORN PLANTS : (Budidaya Teknik Penanaman dan Pemupukan pada Tanaman Jagung Zea Mays) - Tasane, Bois (Uniqbu Journal of Exact Sciences, 2021)
Corn (Zea mays. L.) is an essential requirement for human and animal life. Corn has good nutritional content and crude fiber as a staple food substitute for rice. This study aimed to determine the effect of NPK Phonska fertilizer and plant distance on the growth and production of corn plants. This research is expected to be useful as information material for farmers and related agencies to increase corn production. This research was conducted in Elfule Village, Namrole District, South Buru Regency. The implementation of this research was started from January 2020 to March 2020. The tools used in this research were hoe, machete, meter (measuring instrument. In contrast, the materials used in this study were corn seeds, NPK Phonska fertilizer. This research used a randomized block design. (RBD) Factorial pattern. The results showed that corn plants have unbranched stems. It tends to be cylindrical and consists of several segments and knuckles. Some shoots later will grow into cobs, male flowers, and female flowers in the knuckle in separate maize (diklin) in one plant (monoecious). Male cornflowers are ready for pollination 2-5 days earlier than female flowers (protandry), picking corn to be consumed as corn on the cob does not have to wait until the seeds are ripe. Still, it can be done ± four weeks after the plants’ flower or can take the harvest time between the vegetable corn harvest and the harvest age j great dead cook. Corn cobs are rich in pentose, which is used as a raw material for making furfural. Genetically engineered maize is also now grown as a pharmaceutical producer.